Pragmatyczne aspekty lingwistyki interkulturowej (ze szczególnym uwzględnieniem stosunków polsko-wschodniosłowiańskich) - Kiklewicz, Aleksander (Studia Rossica Posnaniensia, 2015)
A cultural situation is defined as a group of individuals (usually organized groups of entities), functional systems (such as politics, science, religion, sports, the mass media, education, the military, etc.), conceptual systems (including systems of values) as well as forms in which they are manifested, and of relevant environments – ecological, economic, existential ones, etc. (i.e. the stage of events). The author presents a semiotic model of discourse which is founded on four categories: pragmatics, semantics, the form / structure of a message and the context (of a given speech act). The author shows (mainly based on the example of the Eastern European cultural area) the volatility of the relationship between these categories depending on the type of cultural situations. Separate sections describe the pragmatic parameters of a cultural situation: the intensity of the pragmatic / persuasive function as well as the degree of expressiveness, ceremoniousness, politeness and stylistic differentiation of language and the monologism vs. dialogism dichotomy.